Interactive Ebook to Help Young Adults Face Quarter Life Crisis in Modern Era - Tan, Liana (Indonesian Journal of Visual Culture, Design, and Cinema, 2024)
This project aims to help Indonesian young adults gain knowledge on how to overcome quarter-life crisis through Filosofi Teras Interactive eBook while also using interactivity as a strength to gain their interest. The method used is In-depth interview (qualitative) with the target market and the experts. The results is proven that the target market has a level of interest towards quarter life crisis and reading however traditional books is not enough to keep their attention. Interactive eBook therefore is suitable to convey the content of the books with its illustration, animation, audio, and interactivity. Interactive eBook can help the target market to focus and enjoy reading by looking at the animation and keep their attention by curiosity what will happen on the next page.